One‐step affinity capture and precipitation for improved purification of an industrial monoclonal antibody using Z‐ELP functionalized nanocages. Issue 2 (30th October 2017) - Swartz, Andrew R.; Xu, Xuankuo; Traylor, Steven J.; Li, Zheng J.; Chen, Wilfred
Abstract: Protein A chromatography has been identified as a potential bottleneck in the monoclonal antibody production platform, leading to increased interest in non‐chromatographic capture technologies. Affinity precipitation using environmentally responsive, Z‐domain‐elastin‐like polypeptide (Z‐ELP) fusion proteins has been shown to be a promising alternative. However, elevated temperature and salt concentrations necessary for precipitation resulted in decreased antibody monomer content and reduced purification capacity. To improve upon the existing technology, we reported an enhanced affinity precipitation of antibodies by conjugating Z‐ELP to a 25 nm diameter, self‐assembled E2 protein nanocage (Z‐ELP‐E2). The enlarged scale of aggregate formation and IgG‐triggered crosslinking through multi‐valent binding significantly outperformed traditional Z‐ELP‐based methods. In the current work, we sought to develop an affinity precipitation process capable of purifying industrial monoclonal antibodies (mAbs) at ambient temperature with minimal added salt. We discovered that the mAb‐nanocage complex aggregated within 10 min at room temperature without the addition of salt due to the enhanced multi‐valent cross‐linking. After precipitating out of solution, the complex remained insoluble under all wash buffers tested, and only resolubilized after a low pH elution. Through optimization of key process steps, the affinity precipitation yield and impurity clearance met or exceeded protein A chromatography performance with 95% yield, 3.7 logs host cell protein reduction, and >5 logs of DNA reduction from mAb cell culture. Because of the operational flexibility afforded by this one‐step affinity capture and precipitation process, the Z‐ELP‐E2 based approach has the potential to be a viable alternative to platform mAb purification. Abstract : Increased monoclonal antibody demand and upstream productivity have challenged the current downstream purification platform. As an alternative to protein A chromatography, Swartz et al. developed an improved antibody affinity precipitation process using Z‐domain‐elastin‐like polypeptide functionalized nanocages. After optimization of key process parameters, an industrial monoclonal antibody was rapidly captured and precipitated from cell culture without the addition of heat or salt, and the affinity precipitation yield and impurity clearance met or exceeded protein A chromatography performance.